Microvascular Endothelial Dysfunction in Sedentary, Obese Humans Is Mediated by NADPH Oxidase: Influence of Exercise Training - La Favor, Justin D.; Dubis, Gabriel S.; Yan, Huimin; White, Joseph D.; Nelson, Margaret A.M.; Anderson, Ethan J.; Hickner, Robert C. (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—The objectives of this study were to determine the impact of in vivo reactive oxygen species (ROS) on microvascular endothelial function in obese human subjects and the efficacy of an aerobic exercise intervention on alleviating obesity-associated dysfunctionality. APPROACH AND RESULTS—Young, sedentary men and women were divided into lean (body mass index 18–25; n=14), intermediate (body mass index 28–32.5; n=13), and obese (body mass index 33–40; n=15) groups. A novel microdialysis technique was utilized to detect elevated interstitial hydrogen peroxide (H2O2) and superoxide levels in the vastus lateralis of obese compared with both lean and intermediate subjects. Nutritive blood flow was monitored in the vastus lateralis via the microdialysis-ethanol technique. A decrement in acetylcholine-stimulated blood flow revealed impaired microvascular endothelial function in the obese subjects. Perfusion of apocynin, an NADPH oxidase inhibitor, lowered (normalized) H2O2 and superoxide levels, and reversed microvascular endothelial dysfunction in obese subjects. After 8 weeks of exercise, H2O2 levels were decreased in the obese subjects and microvascular endothelial function in these subjects was restored to levels similar to lean subjects. Skeletal muscle protein expression of the NADPH oxidase subunits p22, p47, and p67 was increased in obese relative to lean subjects, where p22 and p67 expression was attenuated by exercise training in obese subjects. CONCLUSIONS—This study implicates NADPH oxidase as a source of excessive ROS production in skeletal muscle of obese individuals and links excessive NADPH oxidase–derived ROS to microvascular endothelial dysfunction in obesity. Furthermore, aerobic exercise training proved to be an effective strategy for alleviating these maladies.